2014
DOI: 10.1128/aem.00429-14
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Ethanol-Responsive Small RNAs in Zymomonas mobilis

Abstract: bZymomonas mobilis is a bacterium that can produce ethanol by fermentation. Due to its unique metabolism and efficient ethanol production, Z. mobilis has attracted special interest for biofuel energy applications; an important area of study is the regulation of those specific metabolic pathways. Small RNAs (sRNAs) have been studied as molecules that function as transcriptional regulators in response to cellular stresses. While sRNAs have been discovered in various organisms by computational prediction and expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 54 publications
3
58
0
Order By: Relevance
“…For example, small RNAs (sRNAs) and 5′UTR in Z. mobilis have been studied recently by transcriptomics and bioinformatics approaches, and the result suggested that sRNAs potentially can be developed as novel biological parts to improve the tolerance against various inhibitors in Z. mobilis (Cho et al 2014(Cho et al , 2017.…”
Section: Discussionmentioning
confidence: 99%
“…For example, small RNAs (sRNAs) and 5′UTR in Z. mobilis have been studied recently by transcriptomics and bioinformatics approaches, and the result suggested that sRNAs potentially can be developed as novel biological parts to improve the tolerance against various inhibitors in Z. mobilis (Cho et al 2014(Cho et al , 2017.…”
Section: Discussionmentioning
confidence: 99%
“…We selected two sRNAs responsive in expression level to ethanol stress, Zms4 (280 nt) and Zms6 (304 nt) of Z. mobilis (44). A RIP-seq experiment was performed by tagging each sRNA with 2-MS2 RNA.…”
Section: Resultsmentioning
confidence: 99%
“…Using transcriptome analysis combined with computational predictions, Cho et al . () identified and validated 15 novel sRNAs in Z. mobile under ethanol stress, and three of them (Zms2, Zms4 and Zms6) exhibited differential expression between aerobic and anaerobic conditions, when low and high ethanol yield was observed respectively. In addition, Zms2, Zms6 and Zms18 exhibited differential expression under 5% ethanol stress conditions, indicating that in Z. mobile , sRNAs may play an important role in ethanol tolerance (Cho et al .…”
Section: Noncoding Rna Related To Biofuel Tolerancementioning
confidence: 91%